2019
DOI: 10.1055/s-0039-3402723
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Reduced Blood Concentrations of Free Carnitine and Acylcarnitines in Infants with Cystic Fibrosis

Abstract: Objective Cystic fibrosis (CF) is a multisystemic inherited disease. The aim of this study was to determine free carnitine (FC) and acylcarnitine concentrations in CF newborns with various mutations of the CFTR gene perinatally. Study Design FC/acylcarnitines were determined in dried blood spots via liquid chromatography-tandem mass spectrometry (LC-MS/MS) on the third day of life of full-term normal (n = 50) and CF (n = 28) newborns. For infants with elevated immunoreactive trypsinogen values, FC/ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…Finally, the analysis of TG in saliva may help to select the patients that need to be treated and to monitor the therapy effects. Despite the lower levels of AC reported in cord blood and in serum from newborn with CF 43 , we found that AC was increased in saliva from adult CF patients, in agreement with the slight increase reported in serum from adult CF patients 44 . The results are consistent with the lipogenesis activation and with the decreased activity of β-oxidation of fatty acids in CF 45 .…”
Section: Discussionsupporting
confidence: 87%
“…Finally, the analysis of TG in saliva may help to select the patients that need to be treated and to monitor the therapy effects. Despite the lower levels of AC reported in cord blood and in serum from newborn with CF 43 , we found that AC was increased in saliva from adult CF patients, in agreement with the slight increase reported in serum from adult CF patients 44 . The results are consistent with the lipogenesis activation and with the decreased activity of β-oxidation of fatty acids in CF 45 .…”
Section: Discussionsupporting
confidence: 87%